Difficulties in organizing the education and upbringing of visually impaired children of preschool age - Raximova Feruzaxon Muxammadjonovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Blindness and low vision from the point of view of special pedagogy is a category of psychophysical disorders, manifested in the limitation of visual perception or its absence, which affects the entire process of formation and development of personality. In persons with visual impairments arise specific features of activity, communication and psychophysical development.